Analisis Pengaruh Environmental, Social, Governance (ESG) Disclosure dan Research & Development Intensity Terhadap Financial Performance Pada Perusahaan Manufaktur yang Terdaftar di BEI - Adenina, Annisa Frecilia; Sudrajat, Sudrajat (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Sustainability and innovation are investment activities as part of a business strategy that needs to be implemented to strengthen the company's position and maximize company performance. The manufacturing sector is a vital sector for the country, but in its operations, much attention is still needed to its impact on the environment and society. This study aims to examine the influence of ESG disclosure and R&D intensity on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. This research is a quantitative descriptive study using secondary data in the form of annual reports and sustainability reports obtained from the official websites of the sample companies and the official website of the Indonesia Stock Exchange. The sample in this study was selected using purposive sampling, resulting in 14 sample companies with a total of 42 observations. This study uses stakeholder theory, legitimacy theory, and signaling theory. Based on the research results, it was found that ESG disclosure and R&D intensity simultaneously affect the company's financial performance, proxied by the return on assets (ROA) ratio. Furthermore, environmental disclosure, social disclosure, and governance disclosure do not affect the company's financial performance, and R&D intensity has a positive effect on the company's financial performance.